Sexualidade em debate: o uso das tecnologias digitais de informação e comunicação como estratégia para a educação sexual de adolescentes no contexto escolar - Silva, Jussara Marta da (2024)
Adolescence is characterized as a challenging stage marked by physical and emotional transformations. It is beneficial for a family, school and health team support network to provide support to these young people. During this period, sexuality emerges and with it the challenges intensify, especially when these young people are inserted in an environment of social vulnerability. In this context, the family does not always help, as sexuality is full of myths and taboos. Thus, the school plays a fundamental role in disseminating, in a scientific way, this topic. The use of innovative practices, such as those from Digital Information and Communication Technologies (DICT) can be useful tools for disseminating knowledge. Digital media, as they are accessible and present in the daily lives of teenagers, prove to be a digital teaching resource capable of contributing to the learning process. Among them, the podcast is an DICT option, as it is easy to access and allows for continuous content renewal. This work aims to promote debate and awareness on the topic of sexuality in basic education, using the podcast as a teaching strategy. For this, 35 students were chosen from a 3rd year high school class at a state public school, located in the municipality of Camaragibe/PE. The methodological strategy used was an investigative didactic sequence, using DICT as a tool, more precisely the construction of a podcast. Initially, the researcher taught a workshop in the classroom, where students learned about the tools necessary for the production and dissemination of this DICT, and in which four students were chosen to participate in the interviews. Secondly, to plan the podcasts, a questionnaire was administered to obtain information about the students' prior knowledge and choose topics for the interviews. The selected themes were sexuality x anxiety, gender-based violence, STIs and teenage pregnancy, from which the students carried out research to understand the theme and created interview scripts. The researcher contacted professionals in the chosen areas and the podcasts were recorded in person and online. In the classroom, students were divided into groups to listen and debate each of the podcasts. To systematize what they learned, the students made mind maps and publicized them at school with posters. On podcast and social media platforms, the publication was made by the researcher. Concluding the study, a digital and printed teaching guide was produced for basic education teachers. It contains a QR Code that directs you to all episodes and a link with the transcription of the audios for deaf people to access. It was noticed that by using digital technologies as facilitators, the project aroused the students' curiosity and attention, encouraging them to reflect and take on youth leadership. It is hoped that this work will contribute as an auxiliary instrument for teachers to use in their classes, as tools to make investigative teaching and learning more meaningful.